Method and system for determining the number and position of damping elements of building structures. - Noorzaei, Jamaloddin; Hejazi, Farzad; Jaafar, Mohd Salleh; Thanoon, Waleed Abdulmalik (2010)

(untitled)
A three dimensional nonlinear viscous damper modeling method applicable in reinforced concrete structures. The analytical model for this three dimensional (3D) nonlinear damper (100) proposed in the present invention consists of three different zones. The first zone is the rigid block zone located (110) at each end of each damping element (100). The second zone is a 3D plastic hinge zone (120) at each end assumed to have zero length. The remaining intermediate part of the member represents the third zone which has the damper function of element (130). These zones represent the finite width of the damper joints, the inelastic and the elastic properties of the member (100).